Introducing Vala programming : a language and techniques to boost productivity - Lauer, Michael (Apress, 2019)
Get an introduction into the Vala programming language and learn about its syntax, semantics, and idioms. Do you want to boost your productivity? Are you interested in a programming language that combines the efficiency of a scripting language with the performance of a compiled language? Did you always want to write GTK+ or GNOME programs, but hate C with a passion? Read this book and learn Vala! Introducing Vala Programming starts from Hello World and goes up to graphical user interfaces using GTK+, covering DBus interprocess communication, network programming, Linux specifics, and more. Youll learn how to leverage external libraries and enhance Vala by writing bindings to new libraries. You will: Discover the Vala programming language and how to use it to boost your productivity Use Vala syntax and semantics Write object-oriented code with Vala Work with DBus Implement networking with Vala Integrate and use external libraries with bindings and libgusb.